The role of punokawan stories in writing learning for young learners - Veronika Unun Pratiwi; Farida Nugrahani; Meidawati Suswandari (Universitas PGRI Madiun, 2023)
Writing skills is critical not only in school, but also in everyday life, that can be accomplished by combining learning media with local resources such as Punokawan wayang figures. This study is objectively focused at comprehending exploratory studies to and characterizing the presence of picture story textbooks linked to writing skills based on Wayang punokawan, as well as conducting a requirements analysis of the picture story book textbooks used. This study a qualitative study which technically used content analysis to collect the data. The presentation of data analysis used an informal presentation method, namely the presentation of data in the form of formulations based on the collection of words. The methods comprised an in-depth interview with key informants; field survey at the location and documentation study. The results of this study obtained that planning for the preparation of textbook guides with the characters of puppet-servants to be used by teachers when teaching. Implementing writing theories, as well as drawing characters in line with the prepared literacy; supervising the implementation process related to learning writing skills, telling stories according to teacher and student handbooks, as well as modules and companion books used during learning.